Vaccine hesitancy comes in waves - Sabat, Iryna (2023)
Funding Information: Authors’ contributions: All authors contributed to the manuscript. IS, TS and JS conceptualized the idea and developed the methodology of the study. IS conducted the formal analysis, investigation and data visualizations and wrote the original draft. JE, JS, TS, PPB, WB, SNB and AT provided critical revisions and validation. IS and SNB equally contributed to the design and implementation of the survey with expertise and feedback from PPB, WB, JE, AT, JS and TS. Tom Stargardt and Jonas Schreyögg equally contributed to the study and should be regarded as Senior authors. Iryna Sabat, Jonas Schreyögg, Tom Stargardt, had full access to all the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis. Funding: This project received funding from the Horizon 2020 Research and Innovation Programme of the European Union through the Marie Skłodowska-Curie Grant Agreement No. 721402 coordinated by the University of Hamburg in Germany and was further funded by the German Research Foundation (DFG) under grant number 466310982. The work was also supported by funding under the Excellence Strategy by the German federal and state governments, as well as by the University of Hamburg, Erasmus University Rotterdam, Bocconi University and Nova School of Business& Economics Lisbon – Chair BPI | “Fundacão La Caixa” on Health Economics. Role of the Funder/Sponsor: The Funding organisations had no role in the design and conduct of the study; collection, management, analysis, or interpretation of the data; preparation, review, or approval of the manuscript; or decision to submit the manuscript for publication. Conflict of Interest Disclosures: All authors have completed the ICMJE Form for Disclosure of Potential Conflicts of Interest (available on request from the corresponding author) and declare: no financial relationships with any organizations that might have an interest in the submitted work, no other relationships or activities that could appear to have influenced the submitted work. Disclaimer: Any opinions, findings, and conclusions or recommendations expressed in this material are those of the authors and do not necessarily reflect the views of the affiliated institutions. Additional Contributions: We would like to thank our colleagues in the ECOS consortium for their cooperation in this project. We especially want to thank our translators Joana Pestana, Elisabetta Oliveri, Maarten Husen, Julien Bergeot, Lasse Falk, who translated the questionnaire into their native languages. Publisher Copyright: © 2023 The Authors